Efeitos do programa de promoção da saúde baseada em mindfulness (PSBM) na qualidade de vida de familiares cuidadoras de pessoas com deficiência intelectual: estudo controlado e randomizado - Oliveira, Letícia Souza [UNIFESP] (2019)
Family caregivers are described in the literature as a population vulnerable to high levels of stress and impaired quality of life. As an example, we selected to compose the sample of this research, relatives of people with moderate intellectual disability (ID). Thinking of techniques that could contribute to a better quality of life of these families, we associate mindfulness, which has extensive studies proving decreased stress and increased quality of life in various populations, to family caregivers of people with ID. As no studies conducted in Brazil relating these two themes were found so far, the results collaborate with the scientific expansion. Objective: To analyze the effects of the Mindfulness Based Health Promotion (PSBM) program on the quality of life of relatives of people with ID. Method: Pragmatic randomized controlled trial that adapted to institutional conditions. Caregivers of 164 caregivers with moderate intellectual disabilities, adolescents and adults, from the APAE Rehabilitation Service of São Paulo were invited to participate and randomly divided into two groups, mindfulness intervention and active control with Problem Solving Training. The groups took place simultaneously, lasted 8 meetings and was held in waiting room time. The primary outcome was the quality of life and the secondary outcome was the caregiver burden. As explanatory variables were considered anxiety, depression, functionality and level of attention to the present moment (mindfulness). We conducted before and immediately after programs, focus group, sociodemographic questionnaire, World Health Organization Quality of Life instrument (WHOQOL-bref), Informal Caregiver Overload Assessment Questionnaire, World Health Organization Disability Assessment Schedule (WHODAS 2.0), Hospital Anxiety and Depression Scale HADS, Mindful Attention Awareness Scale, Semi-structured Qualitative Analysis Questionnaire. There was no follow up. Results: Most participants were mothers (94%), with an average age of 56 years and son of 24 years, on average. More than half of the caregivers were relatives of patients with moderate ID Down syndrome (55%). A delta analysis, without comparing the media difference (Δ) of the variations applied before and after the intervention, confirmed improvements in caregiver burden of 0.0039 in the overall index and 0.0253 in 'personal life implications', sub-item of this. same scale. Improvement of anxiety variables, functionality and level of attention to the moment were considered explanatory for this result, according to linear regression analysis. The number needed to treat informal caregiver burden was calculated at 3. According to a qualitative analysis, mindfulness used as a tool to cope with the demands, the caregivers' dangerous self-efficacy in the individual, while the control group strengthened the group's sentiment. Conclusion: the intervention was effective to reduce caregiver burden and the control group did not achieve statistically used results in the delta statistical analysis. The intervention acted to increase the individual self-efficacy of the caregivers, while the control group showed a strengthening of the group feeling.